Peran Visum Et Repertum Sebagai Alat bukti Dalam Perkara Tindak Pidana Kekerasan Bersama (Studi Putusan No. 348/Pid.B/2021/PN.Amb) - Masriawati Yuliana; Sherly Adam; Denny Latumaerissa (Faculty of Law Universitas Pattimura, 2023)
Expert testimony is a doctor's statement that can help investigators in providing evidence. The doctor's opinion should be stated in writing in the form of a health report called Visum Et Repertum. The research method used is normative legal research. The nature of the research is descriptive analysis by examining literature material using the Law approach, Concept Approach and Case Approach. The use of legal source materials consists of primary and secondary legal materials to discuss problem formulation. The research results show that: Visum et Repertum does not absolutely have to be present, but in criminal acts where the object is the human body, for example murder, assault, rape, it is best to be equipped with a Visum et Repertum. If several witnesses saw the occurrence of a crime, for example violence or abuse and this is supported by the defendant's statement and the judge is convinced of the defendant's guilt, then the defendant can be sentenced even if it is not accompanied by a Visum et Repertum. However, if there is a lack of evidence, Visum et Repertum can be used as evidence to strengthen the proof of a violent crime committed by someone. The position of post mortem et repertum even though the content is in the form of expert testimony given under oath and outside of a court hearing, and its qualifications are included as documentary evidence and not expert testimony evidence, and the qualifications are included as documentary evidence and not expert testimony evidence. And if the post mortem et repertum is linked to Article 1 stb. 1937 No. 350 can also be considered as expert testimony and expert testimony is valid evidence in article 184 KUHAP.